2010
DOI: 10.4300/jgme-d-09-00073.1
|View full text |Cite
|
Sign up to set email alerts
|

On-site Night Float by Attending Physicians: A Model to Improve Resident Education and Patient Care

Abstract: A night-float system that includes on-site attending physician supervision can provide a valuable opportunity for resident education and may help improve the quality of patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…In 2010, Defilippis et al reported a high level of resident satisfaction regarding patient care when an attending was present in the hospital for 6 hours each night. 13 Residents also felt the on-site attending was helpful with patient evaluations and developing treatment plans. Although results were not directly compared to those without attending hospitalists present, they were substantially better than historical results at the same hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, Defilippis et al reported a high level of resident satisfaction regarding patient care when an attending was present in the hospital for 6 hours each night. 13 Residents also felt the on-site attending was helpful with patient evaluations and developing treatment plans. Although results were not directly compared to those without attending hospitalists present, they were substantially better than historical results at the same hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a positive attitude and perception of value are thought to be very important for learning, and these were clearly improved by direct supervision overnight. [11][12][13]15 Figure 1. Neurology resident perceptions of educational and clinical value of night float rotation are improved by an on-site neurohospitalist.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to night medicine, interns on night float rotations typically have little faculty interaction, leading to fewer opportunities for bedside teaching and observation of direct patient care. [2][3][4] Multiple studies have highlighted residents' perceptions of night float rotations as predominantly service-focused time with few formal educational opportunities. [4][5][6][7] While night float rotations have been valued for their experiential learning potential, they have historically lacked a formalized educational component.…”
Section: Introductionmentioning
confidence: 99%
“…9 Challenges inherent in night float rotations include cross-coverage responsibilities and resident fatigue, leading to decreased alertness. 10 Two studies 2,3 showed perceived improvements in the value of care delivered and in resident education with the presence of dedicated, on-site, attending physicians. Critics, however, argue that this structure has a negative effect on resident autonomy overnight, decreasing the experiential learning component of such rotations that is felt to be so valuable to the professional maturation of resident physicians.…”
mentioning
confidence: 99%
“…4 In response, various medical and surgical specialties have developed duty hour compliance systems without substantial ill effect on surgical case volume or other educational outcomes. 5,6 To meet the 2011 ACGME standards, the Oregon Health & Science University (OHSU) neurological surgery residency program instituted a novel 3-person night float system in January 2011. 2 Here we describe the planning and implementation of this new system and analyze resident duty hour violations, number of operative cases logged, and resident acceptance of duty hour regulations for 12 months before and 12 months after institution of the new system.…”
Section: Introductionmentioning
confidence: 99%